2019
DOI: 10.1101/713164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EuRBPDB: a comprehensive resource for annotation, functional and oncological investigation of eukaryotic RNA binding proteins (RBPs)

Abstract: These authors contributed equally to this work. 3 1 1 , 5 7 1 RBPs with RBDs and 3,639 non-canonical RBPs without known RBDs. EuRBPDB provides detailed annotations for each RBP, including basic information and functional annotation. Moreover, we systematically investigated RBPs in the context of cancer biology based on published literatures and large-scale omics data. To facilitate the exploration of the clinical relevance of RBPs, we additionally designed a cancer web interface to systematically and interacti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Given the DECTG motif, the potential binding proteins were predicted using the databases of EuRBPDB (http://eurbpdb.syshospital. org/index.php), 17 RegRNA 2.0 (http://regrna2.mbc.nctu.edu.tw/ index.html), 18 and ATtRACT (https://attract.cnic.es/). 19 Nuclear cap-binding subunit 3 (NCBP3), EWS RNA binding protein 1 (EWSR1), and developmentally regulated GTP binding protein 2 (DRG2) were identified as the candidates with top three confidential scores ( Figure 6A) and also as DEGs in MH and SH compared to NC in vivo and in vitro (Table S3).…”
Section: Translation Process Facilitated By Dectg Motif Binding Protementioning
confidence: 99%
“…Given the DECTG motif, the potential binding proteins were predicted using the databases of EuRBPDB (http://eurbpdb.syshospital. org/index.php), 17 RegRNA 2.0 (http://regrna2.mbc.nctu.edu.tw/ index.html), 18 and ATtRACT (https://attract.cnic.es/). 19 Nuclear cap-binding subunit 3 (NCBP3), EWS RNA binding protein 1 (EWSR1), and developmentally regulated GTP binding protein 2 (DRG2) were identified as the candidates with top three confidential scores ( Figure 6A) and also as DEGs in MH and SH compared to NC in vivo and in vitro (Table S3).…”
Section: Translation Process Facilitated By Dectg Motif Binding Protementioning
confidence: 99%
“…We reanalyzed microarray expression data of samples from 64 medulloblastoma patients to analyze RNA-binding proteins (RBPs) expression in patients across the four reported sub-groups [ 35 ]. Among a list of 1220 canonical RBPs represented on the microarray [ 36 ], we found that YBX1 is ubiquitously expressed in medulloblastoma patient samples across all sub-types and ranks among the top expressed RBPs on average ( Figure 1 a). However, there was no clustering of the medulloblastoma subgroups SHH, WNT, group 3 and group 4 based on YBX1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…The lncRNAs were applied to analyze their possible binding proteins using the web interface of lncSEA, a new comprehensive human lncRNA sets resource and enrichment analysis platform which also integrates RNA binding proteins rooted in large-scale crosslinking-immunprecipitation sequencing (CLIP-Seq) data from StarBase, RNAInter (RNA interactome database) and EuRBPDB (a comprehensive and user-friendly database for eukaryotic RNA binding proteins) [32][33][34][35].…”
Section: Identi Cation Of the Cerna-gene Relationship Pairsmentioning
confidence: 99%